2011 13th International Conference on Transparent Optical Networks 2011
DOI: 10.1109/icton.2011.5971173
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thickness and doping on the nonlinear absorption behaviour of IIIA-VIA group amorphous semiconductor thin films

Abstract: The nonlinear optical absorption of InSe, GaSe and Ga x In 1-x Se amorphous films with varying thickness and doping has been studied by open-aperture Z-scan experiment with 4 ns and 65 ps pulse durations at 1064 nm wavelength and femtosecond pump-probe spectroscopy. Our results show that the dopant and film thickness (from 20 nm to 104 nm) results in switching from saturable absorption to nonlinear absorption for equal input intensities. This behaviour is attributed to increasing localized defect states with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…To evaluate the data collected from OA Z-scan curves, we used a model incorporating one photon absorption (OPA), two photon absorption (TPA), free carrier absorption (FCA), and their saturations. [1,2,18] dI dz…”
Section: Nla Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate the data collected from OA Z-scan curves, we used a model incorporating one photon absorption (OPA), two photon absorption (TPA), free carrier absorption (FCA), and their saturations. [1,2,18] dI dz…”
Section: Nla Parametersmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Our previous studies revealed that the saturation thresholds and effective NLA coefficients in both amorphous and polycrystalline semiconductor thin films can be controlled by altering the film thickness and/or doping. [1][2][3]9,17,18] The aim of this study is to investigate the effect of both Al doping and co-doping on structural, optical, and nonlinear optical properties. Although dopant atom ionic radii and valence electrons play an important role on defect states of the material, selection of sol-gel dip coating method allows thin films to be deposited in polycrystalline form therefore make it possible to also study and understand defects originating from grain boundaries since polycrystalline materials are composed of a large number of grains.…”
Section: Introductionmentioning
confidence: 99%